The Logical Status of Fictional Speech - Zuluaga, Francisco (Íkala, Revista de Lenguaje y Cultura, 1996)
I believe that speaking or writing in a language consists of performing these speech acts of a very specific type called "illocutionary acts". These include making assertions, asking questions, giving orders, making promises, apologizing, thanking, and so on. Likewise, I believe that there is a systematic configuration of relations between the meanings of the words and sentences we utter and the illocutionary acts we perform in uttering those words and sentences.